Merry, merry ghost - Hart, Carolyn G. (Hart, Carolyn G. Bailey Ruth ghost mysteries, 2009)
Being dead can't put a damper on spirited, holiday-loving Bailey Ruth Raeburn. Christmas is a time for family and giving, and a wealthy woman in Adelaide, Oklahoma, is about to embrace both. Discovering that she has a young grandson, the dowager decides to change her will to leave the bulk of her fortune to the young boy - an alteration that stuns the rest of her family. But a scrooge of a determined heir makes sure she never signs the new document. When she is found dead, it's up to that irrepressible spirit Bailey Ruth, on assignment from Wiggins and Heaven's Department of Good Intentions, to protect a little boy, foil a murderer, and save Christmas. There's only one teeny hitch: how can Bailey Ruth figure out which family member was desperate enough to kill when everyone has a motive?